Material implication (rule of inference)

In propositional logic, material implication[1][2] is a valid rule of replacement that allows for a conditional statement to be replaced by a disjunction in which the antecedent is negated. The rule states that P implies Q is logically equivalent to not-P or Q and that either form can replace the other in logical proofs.

${\displaystyle P\to Q\Leftrightarrow \neg P\lor Q}$

Where "${\displaystyle \Leftrightarrow }$" is a metalogical symbol representing "can be replaced in a proof with."

Formal notation

The material implication rule may be written in sequent notation:

${\displaystyle (P\to Q)\vdash (\neg P\lor Q)}$

where ${\displaystyle \vdash }$ is a metalogical symbol meaning that ${\displaystyle (\neg P\lor Q)}$ is a syntactic consequence of ${\displaystyle (P\to Q)}$ in some logical system;

or in rule form:

${\displaystyle {\frac {P\to Q}{\neg P\lor Q}}}$

where the rule is that wherever an instance of "${\displaystyle P\to Q}$" appears on a line of a proof, it can be replaced with "${\displaystyle \neg P\lor Q}$";

or as the statement of a truth-functional tautology or theorem of propositional logic:

${\displaystyle (P\to Q)\to (\neg P\lor Q)}$

where ${\displaystyle P}$ and ${\displaystyle Q}$ are propositions expressed in some formal system.

Example

An example is:

If it is a bear, then it can swim.
Thus, it is not a bear or it can swim.

where ${\displaystyle P}$ is the statement "it is a bear" and ${\displaystyle Q}$ is the statement "it can swim".

If it was found that the bear could not swim, written symbolically as ${\displaystyle P\land \neg Q}$, then both sentences are false but otherwise they are both true.

References

1. ^ Hurley, Patrick (1991). A Concise Introduction to Logic (4th ed.). Wadsworth Publishing. pp. 364–5.
2. ^ Copi, Irving M.; Cohen, Carl (2005). Introduction to Logic. Prentice Hall. p. 371.